The Necessary Illusion – Giannotti on Fetishism - Repa, Luiz (Revista Eletrônica Estudos Hegelianos, 2024)
The main aim of this article is to investigate the most fundamental meanings that José Arthur Giannotti attributes to the phenomenon of fetishism in Marx. His interpretation, as expounded in Certa herança marxista [Certain Marxist Heritage] and grounded in the concept of a necessary illusion in a predominantly Kantian sense, appears to challenge a fundamental aspect of the new readings that Uspian Philosophical Marxism, with Giannotti as a key figure, has advanced since the 1960s. These new readings have underscored the notion of real abstraction as the foundation of commodity fetishism in a predominantly Hegelian sense. The article aims to clarify that Giannotti's interpretation does not aim to replace one perspective with another but rather to integrate the initial insights of the critique of real abstraction with the illusory measurement practices inherent in the process of production and exchange of commodities.
Keywords: Uspian Philosophical Marxism; Fetishism; Real Abstraction; Necessary Illusion